2017
DOI: 10.3920/bm2016.0144
|View full text |Cite
|
Sign up to set email alerts
|

The positive benefit of Lactobacillus paracasei NCC2461 ST11 in healthy volunteers with moderate to severe dandruff

Abstract: Dandruff is a common persistent, relapsing inflammatory condition affecting the scalp. An imbalanced proportion of the major bacterial and fungal populations colonising the scalp, a skin barrier dysfunction, and hyperseborrhoea are three main etiological factors of dandruff. The efficacy of Lactobacillus paracasei NCC 2461 ST11 (ST11) to manage dandruff and to restore a balanced scalp microbiome was assessed. Sixty healthy male volunteers aged 18 to 60 years with moderate to severe dandruff consumed on a daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 29 publications
0
37
0
1
Order By: Relevance
“…Some deviations have been detected in the intestinal mucosa of patients with seborrheic dermatitis [287]. A clinical study on probiotics consumption (Lactobacillus paracasei strain) found significant improvements in severity and symptoms of moderate to severe dandruff compared to a placebo treatment [126]. However, the influence of the gut microbiome composition on seborrheic dermatitis and dandruff remains to be elucidated.…”
Section: Gut Microbiome and Diet Implications In Dandruff And Seborrhmentioning
confidence: 99%
“…Some deviations have been detected in the intestinal mucosa of patients with seborrheic dermatitis [287]. A clinical study on probiotics consumption (Lactobacillus paracasei strain) found significant improvements in severity and symptoms of moderate to severe dandruff compared to a placebo treatment [126]. However, the influence of the gut microbiome composition on seborrheic dermatitis and dandruff remains to be elucidated.…”
Section: Gut Microbiome and Diet Implications In Dandruff And Seborrhmentioning
confidence: 99%
“…In addition to the pathologies mentioned above, new lines of research are being opened to identify possible benefits of treatment with probiotics in other dermatological disorders. These other pathologies in which the influence of the intestinal microbiota and probiotic treatment on its evolution are currently being studied are rosacea [ 73 ], vitiligo [ 74 ], seborrheic dermatitis [ 75 ], hidradenitis suppurativa [ 64 , 75 ], dandruff [ 76 ] and ulcers [ 77 ]. The results in these pathologies are very preliminary and there are no clinical studies with a considerable number of patients, so it will be necessary to wait for the results of the works currently in progress to assess the possible efficacy of probiotics in these other skin disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics have been demonstrated to exert beneficial effects on skin health [ 42 , 43 , 44 ]. For example, a two month supplementation of Lactobacillus paracasei decreased skin sensitivity and increased the rate of barrier function recovery in a placebo-controlled trial [ 43 ].…”
Section: Discussionmentioning
confidence: 99%